2009
DOI: 10.1158/1078-0432.ccr-08-1913
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin as a Candidate Prognostic Biomarker of Ewing's Sarcoma Revealed by Proteomics

Abstract: Purpose: We aimed to identify novel prognostic biomarkers for Ewing's sarcoma by investigating the global protein expression profile of Ewing's sarcoma patients. Experimental Design: We examined the proteomic profile of eight biopsy samples from Ewing's sarcoma patients using two-dimensional difference gel electrophoresis. Three patients were alive and continuously disease-free over 3 years after the initial diagnosis (good prognosis group) and five had died of the disease within 2 years of the initial diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…Accordingly, multivariate analysis is not possible. Similar results are also observed in other solid tumors (Tsui et al, 2008;Kikuta et al, 2009;Coutinho-Camillo et al, 2010). Futhermore, in AML mutated NPM also behaves as a favorable prognostic marker for overall survival or disease-free survival (Shahab et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Accordingly, multivariate analysis is not possible. Similar results are also observed in other solid tumors (Tsui et al, 2008;Kikuta et al, 2009;Coutinho-Camillo et al, 2010). Futhermore, in AML mutated NPM also behaves as a favorable prognostic marker for overall survival or disease-free survival (Shahab et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…that the difference of NPM expression was associated with prognosis and also indicated that NPM may be an important prognosis marker in some solid tumors (Tsui et al, 2008;Kikuta et al, 2009;Coutinho-Camillo et al, 2010). A recent study showed NPM overexpression in CRC and the differential expression of NPM1 along the normal colon-adenoma-carcinoma progression (Wong et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, NPM1 had been found to be mutated in acute myeloid leukemia (AML; Falini et al 2005;Verhaak et al 2005). Over-expression of NPM1 may be associated with tumor recurrence and progression and indicated a poor prognosis in bladder cancer and Ewing's sarcoma (Tsui et al 2004(Tsui et al , 2008Kikuta et al 2009). There are multiple mechanisms associated with the anti-apoptotic process of NPM1.…”
Section: Discussionmentioning
confidence: 99%
“…29 Here we show that reduced NPM protein expression was associated with poor prognosis and that over-expression of NPM in the MDA-MB-231 breast cancer cells abrogated their growth in soft agar, supporting a tumor suppressive function for NPM in breast cancer. Previously, high NPM expression has been associated with poor prognosis or recurrence in Ewing's sarcoma, 48 hepatocellular carcinoma, 34 bladder cancer, 49 prostate cancer, 28 colon carcinoma, 50 and gastric carcinoma. 51 Intriguingly, where data on NPM expression in the corresponding normal tissue was available in these studies, 28,34,50,51 it was markedly lower than in the cancer tissue (NPM expression in normal tissue was not reported for bladder cancer and Ewing's carcinoma).…”
Section: Discussionmentioning
confidence: 99%